Passive and Active Measurement 14th International Conference, PAM 2013, Hong Kong, China, March 18-19, 2013. Proceedings - Roughan, Matthew; Chang, Rocky; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 14th International Conference on Passive and Active Measurement, PAM 2013, held in Hong Kong, China, in March 2013. The 24 revised full papers presented were carefully reviewed and selected from 74 submissions. The papers have been organized in the following topical sections: measurement design, experience and analysis; Internet wireless and mobility; performance measurement; protocol and application behavior; characterization of network usage; and network security and privacy. In addition, 9 poster abstracts have been included.
Measurement Design, Experience and Analysis -- Internet Wireless and Mobility -- Performance Measurement -- Protocol and Application Behaviour -- Characterization of Network Usage -- Network Security and Privacy.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Operating systems (Computers).; Data protection; Computer Science; System Performance and Evaluation; Computer Communication Networks; Operating Systems; Systems and Data Security